A case of availability bias for COVID‐19 causing scrub typhus diagnostic errors. (21st June 2021) - Ihara, Shiichi; Shikino, Kiyoshi; Ikusaka, Masatomi
Abstract : Although patients with scrub typhus develop a maculopapular rash all over the body, patients with COVID‐19 may also show a similar rash. At the first visit, we did not fully inspect his trunk and extremities under his clothes. Although scrub typhus and COVID‐19 have some similar symptoms, an eschar is a characteristic symptom of the former, and careful inspection is important to distinguish between the diseases.